ANALISIS KESULITAN MEMBACA TEKS BAHASA INGGRIS DI KELAS VIII SMP DARUDDA'WAH PUNGGUR KUBU RAYA - Wulandari, Wulandari; ismu Purwaningsih, Dewi (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2025)
This research's background is difficulty reading English texts in eighth-grade students at SMPI Darudda’wah Islamic boarding school punggur kubu Raya Regency. This study aimed to discover what difficulties students experienced when reading English texts and the factors of difficulty reading English texts for class VIII SMPI Darudda’wah punggur. This research was conducted at SMPI Darudda’wah punggur kabupaten kubu raya in june 2024. This research used a descriptive qualitative method with a population of 16 students, sampling was taken using purposive sampling. The data collection techniques used are questionnaires and interviews. Based on the research conducted, it was found that students who had difficulty reading English texts in front of the class, difficulty understanding the contents of the English text, difficulty understanding the content of the material, could not retell the contents of the English text, do assignments only when they received assignments from the teacher. Internal and external factors cause the student to have difficulty reading English texts. The internal factors experienced by students are not reading English texts (81.25%), not taking the time to read English texts (75%), and reading English texts only if instructed by the teacher (81.25%), besides there are external factors that influence students in reading English texts, namely the lack of Support from the family environment (93.75%), the school environment that does not support reading English texts (68.75%), the school has not given serious attention to the aspect of fostering student interest in reading English texts (93.75%).